Online detection of error-related potentials in multi-class cognitive task-based BCIs. Issue 1 (3rd April 2019) - Yousefi, Rozhin; Rezazadeh Sereshkeh, Alborz; Chau, Tom
ABSTRACT: One method for improving the accuracy and hence the rate of communication of a brain–computer interface (BCI) is to automatically correct erroneous classifications by exploiting error-related potentials (ErrPs). The merit of such a correction scheme has been demonstrated in both active (e.g. motor imagery) and reactive (e.g. P300) BCIs. Here, we investigated the effect of ErrP-guided error correction in a three-class, active BCI based on cognitive rather than motor imagery tasks using electroencephalography (EEG). Ten able-bodied adults participated in three sessions of data collection. For each participant, a ternary BCI differentiated among idle state and two personally selected cognitive tasks (e.g. mental arithmetic, counting, word generation, and figure rotation). Real-time feedback of the BCI decision was displayed to the participant following each task. EEG data after feedback onset were used to detect ErrPs and correct the BCI's output in the case of detected errors. ErrP-based error correction modestly but significantly improved the average online task classification accuracy (+7%) as well as the information transfer rate (+0.9 bits/min) of the ternary BCI across participants. Our findings support further study of ErrPs in active BCIs based on cognitive tasks.